Impact of FDI, Labor Productivity and Firm Size on the Export of Indonesian Manufacturing - Galuh Maghvira Pramiswari; Rossanto Dwi Handoyo (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze empirically the impact of foreign direct investment (FDI), labor productivity, and firm size on the company's exports in the Indonesian manufacturing industry and measure the technical efficiency of Indonesian manufacturing industry. The result show that manufacturing industry has yet to achieve the maximum level of technical efficiency. FDI, firm size, technical efficiency, industry concentration, and the use of imported raw materials have a positive and significant impact on the company's export opportunities, meanwhile labor productivity and firm location results in a positive but insignificant relationship to the company's export opportunities. Other findings show that interactions variable between FDI and the use of imported raw materials and interaction between firm size and the use of imported raw materials resulting in a positive and significant relationship to the company's export opportunities, meanwhile interaction between FDI and industry concentration statistically insignificant on the company's export opportunities.